2014
DOI: 10.1088/0022-3727/47/7/075502
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic effect in transition metal modified polycrystalline BiFeO3thin films

Abstract: We report photovoltaic (PV) effect in multiferroic Bi 0.9 Sm 0.1 Fe 0.95 Co 0.05 O 3 (BSFCO) thin films. Transition metal modified polycrystalline BiFeO 3 (BFO) thin films have been deposited on Pt/TiO 2 /SiO 2 /Si substrate successfully through pulsed laser deposition (PLD). PV response is observed under illumination both in sandwich and lateral electrode configurations. The open-circuit voltage (V oc) and the short-circuit current density (J sc) of the films in sandwich electrode configuration under illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…In contrast, the big V OC in BSFCO film with illumination, originated from the reduced junction resistance and increased numbers of domain walls, was controlled by the polarization up and down state. 11 The V OC of BLFNO film shown in Fig. 3 was large, compared to those of no-doped polycrystalline BFO films in inset in Fig.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, the big V OC in BSFCO film with illumination, originated from the reduced junction resistance and increased numbers of domain walls, was controlled by the polarization up and down state. 11 The V OC of BLFNO film shown in Fig. 3 was large, compared to those of no-doped polycrystalline BFO films in inset in Fig.…”
mentioning
confidence: 89%
“…The V OC was about 0.45 V. It was reported that both electrode/ film interface and ferroelectric polarization could make a certain contribution to PV effect of BFO film. 5,[11][12][13] For this reason, also measured was the contribution of ferroelectric polarization to PV effect. The poled-up and poled-down states were acquired by applying bias voltage of À50 V and 50 V (833 kV/cm) to the top ITO electrode.…”
mentioning
confidence: 99%
“…Except for a few cases [47], most cation-doped semiconducting ferroelectric oxide-based devices exhibit energy conversion efficiency under 1% and photocurrent densities on the order of μA cm −2 [45,[48][49][50]. Wang et al [51] demonstrated a new strategy for designing stoichiometric semiconducting perovskite ferroelectric materials.…”
Section: Improvement Of Materials Propertiesmentioning
confidence: 99%
“…During the past years, the development of preparation techniques of BFO films, such as pulse laser deposition [6][7][8], radio frequency magnetron sputtering deposition [9][10][11], and chemical solution deposition [2,3,12], provided new data for understanding of physical properties and leakage current mechanisms of BFO films. Many researchers, such as Kharel et al [13], Puli et al [14], Raghavan et al [15], Wang et al [16], Wen et al [17], and Ding et al [18], etc., have reported the effects of transition metal and/or rare earth ion dopants on the structural, magnetic, electrical and photovoltaic properties of BFO films using the above deposition methods. Among these doping elements, Mn is of special interest and attracts much attention due to the complexity of the Mn valance state in different chemical environments.…”
Section: Introductionmentioning
confidence: 99%